The Impact of Corporate Governance on Financial Performance: (Measured using Accounting and Value-Added based Measures): Evidence from Malaysia - Abdul Aziz, Khairul Annuar (2005)
This paper aims to test empirically which measure, an accounting based financial performance measure such as Return on Equity, Price to Earnings Ratio, Earnings Per Share and Return on Capital Employed; or value-added based financial performance measures such as Economic Value Added and Market Value Added; is more closely related with Corporate Governance Compliance. This paper also aims to study the level of Corporate Governance Compliance of the Smaller Companies listed on the KLSE, the measure of which was done by the size of market capitalisation. The study involves usage of a Corporate Governance Scorecard developed jointly by a research team at Nottingham University Business School (NUBS) Malaysia Campus in collaboration with the Minority Shareholders Watchdog Group (MSWG). The joint research was done on the level of compliance with the recommendations of the Malaysian Code as well additional global best practices incorporated into the Scorecard. The 100 sampled companies were given scores of corporate governance compliance using this Scorecard. The study then involves the use of correlation analysis to link various financial performance measure; both accounting and value-added based; to the corporate governance compliance scores obtained using the Scorecard. Finally the results were then applied to a multi regression model to attest whether collectively value-added based financial performance measures are better predictors in comparison to accounting based financial performance measures. Finally, our results reveals that the corporate governance compliance scoring of the sampled companies was low, and this was conformed when the results were compared to the results of a prior study done on the biggest companies listed on KLSE, measure by market capitalisation. Our results from both the correlation and multiple regression analysis also reveal that value-added based financial performance, individually and collectively, are more correlated and are better predictors of corporate governance compliance then that of their accounting based measures counterparts. Keywords: Corporate Governance, Corporate Performance, Financial Performance, Value-Added Measures; EVA, MVA, Accounting Measures, EPS, PE Ratio, ROE, ROCE